THE ROLE OF RELIGIOUS EDUCATION TEACHER DEVELOPMENT ON THE VALUES OF RELIGIOUS TOLERANCE AT SMAN 8 PONTIANAK: PERAN PEMBINAAN GURU PENDIDIKAN AGAMA PADA NILAI-NILAI TOLERANSI BERAGAMA DI SMAN 8 PONTIANAK - Faisal Abdullah; Mamba'ul Munawarah (SOSIOEDUKASI, 2023)
This study aims to determine the role of religious teachers in instilling religious tolerance values, the forms of tolerance that are being taught, and the factors that support and prevent the instillation of religious tolerance values. This research uses a qualitative approach with the type of phenomenological research. Data was collected through observations, in-depth interviews, documentation, and internet searches. The data analysis used is phenomenological data analysis, which is a method that prioritizes data analysis through phenomena experienced by key informants. The results indicated that religion teachers at SMA Negeri 8 Pontianak served primarily as educators, mentors, models, and role models, in addition to counselors. SMA Negeri 8 Pontianak embraces forms of tolerance, such as mutual aid amongst students of different beliefs, mutual respect for diversity in school, and perpetual peace in the sense that students never argue over the teachings or beliefs of other students. In addition, the delivery of religious tolerance in children is facilitated by good cooperation between school inhabitants and suitable infrastructure and facilities. The cognitive maturity of various students inhibits the process of instilling the ideals of religious tolerance in students, as a result of which the process is inhibited.